Iron(II) Complexes Supported by Sulfonamido Tripodal Ligands: Endogenous versus Exogenous Substrate Oxidation - Cook, Sarah A. (American Chemical Society, 2014)
[Image: see text] High-valent iron species are known to act as powerful oxidants in both natural and synthetic systems. While biological enzymes have evolved to prevent self-oxidation by these highly reactive species, development of organic ligand frameworks that are capable of supporting a high-valent iron center remains a challenge in synthetic chemistry. We describe here the reactivity of an Fe(II) complex that is supported by a tripodal sulfonamide ligand with both dioxygen and an oxygen-atom transfer reagent, 4-methylmorpholine-N-oxide (NMO). An Fe(III)–hydroxide complex is obtained from reaction with dioxygen, while NMO gives an Fe(III)–alkoxide product resulting from activation of a C–H bond of the ligand. Inclusion of Ca(2+) ions in the reaction with NMO prevented this ligand activation and resulted in isolation of an Fe(III)–hydroxide complex in which the Ca(2+) ion is coordinated to the tripodal sulfonamide ligand and the hydroxo ligand. Modification of the ligand allowed the Fe(III)–hydroxide complex to be isolated from NMO in the absence of Ca(2+) ions, and a C–H bond of an external substrate could be activated during the reaction. This study highlights the importance of robust ligand design in the development of synthetic catalysts that utilize a high-valent iron center.